Arbitrage conditions with no short selling (2012)
A key assumption to prove the Fundamental Theorem of Mathematical Finance is the possibility of short selling the risky assets of the market. In this article we exhibit a simple geometric condition to handle the arbitrage opportunities when short selling is not possible. Moreover, this approach provides a pedagogical tool to visualize the consistency of the model when shorting is allowed for only some of the assets. Some examples are presented, both in analytical and graphical ways.